Synthesis of CuO-based Nanofluids Mediated by White Egg for Ethanol Distillation Applications - Aliefia Noor; Evi J; Aisyah D.A.T. Safitri; Rifqi A. Rafsanjani; Yuant Tiandho (Department of Chemistry - Universitas Bangka Belitung, 2020)
The use of solar energy to satisfy renewable energy in Indonesia has great potential. To improve the efficiency of solar collectors, some researchers proposed solar collectors that equipped by nanofluids as working fluids. CuO-based nanofluids are known as nanofluids that have excellent conductivity. The purpose of this study is to synthesise CuO nanofluids through egg white mediation methods, and it will be applied to simple distillation systems. Generally, the synthesising process is arranged based on the modification of the sol-gel method, and by the calcination, it will leave metal oxides, namely CuO-nanoparticles. The calcination temperature variation used is 150℃; 300℃; 500℃ and 700℃. According to Debye-Scherrer equations, it is known that, in optimal condition, we obtain CuO crystallite by the size is 42 nm. The use of CuO nanofluids can increase the conductivity of fluids and can increase the effectiveness of ethanol distillation by 81%.